39Ar dating with small samples provides new key constraints on ocean ventilation - Sven Ebser (Nature Portfolio, 2018)
The rare noble gas isotope 39Ar is the ideal tracer to investigate the ventilation of the deep ocean in the time range of 50 to 1000 years. Here the authors constrain transit time distributions in the eastern Tropical Atlantic with 39Ar-measurements done on a sample size of 5 L of water utilising modern atom-optical techniques.